Effect of Soft-start Curing Mode on Postoperative Hypersensitivity of Class I Posterior Composites Restorations - Betamar, Naeima; Shah, Rupal (Libyan Journal of Dentistry, 2018)
Objectives: To evaluate the occurrence of postoperative hypersensitivity (POH) in Class I posterior composite restorations comparing the soft-start with the constant light curing modes. Materials and Methods: Seventy patients with each having contra lateral class I occlusal caries lesions in premolars and molars teeth were participated. 140 class I cavity preparations were restored with Adper™ Single Bond 2 adhesive and Filtek™ Z250 XT resin composite (3M-ESPE). For each patient, one restoration was cured with soft-start mode and the contralateral restoration was cured with constant curing modes using Light Emitting Diode (LED) curing light. POH to various stimuli was evaluated at week 1, 4, and 13 post-treatment using Visual Analog Scale (VAS). Data were collected and analyzed by Chi-Square and Fischer Exact tests. Results: No statistical significant differences were observed between the two curing modes (soft-start or constant) in occurrence of postoperative hypersensitivity (P>0.05). Out of 140 restorations that were placed, only two (1.4 %) restorations reported POH to cold stimuli at week 1 post-treatment, being in mild; VAS=3 for soft-start and moderate; VAS=5 for constant light curing mode. No POH was reported at week 4 and 13 for soft-start or constant curing modes. Conclusion: Soft-start curing mode did not show any difference in occurrence of POH in class I posterior composite restorations when compared with constant curing mode.